Perception of the Customer Satisfaction Towards Quality Service of Unlimited Buffet in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Unlimited Buffet restaurants, a concept that dates back to the 16th century, are regainingpopularity. Buffets remain one of the most popular alternatives for customers due to theirversatility, diverse food options, and endless servings at a fair price. It is a common style ofmeal service at many restaurants and is regularly utilized at banquet events. This study aimsto determine the significance of service quality in an unlimited buffet restaurant in Quezon Cityfor the success or failure of this business. In line with this, the researchers would like to knowhow customer preferences affect service quality in this kind of food business.According to the results of the study, customers were very satisfied with the service quality,the food quality, and the place; the most common problem encountered with quality servicewas that buffet restaurants' customers could not be satisfied because of time constraints. Thisstudy recommends that restaurants continually retain (grp5 4212)their ability to prepare foodquickly.Customer satisfaction with the unlimited buffet would be advantageous to the business. Tosustain customer satisfaction, it is recommended that the business continue to implementquality services such as service quality, food quality, and place. Researchers recommendutilizing time management to make the most of the restaurant's allotted time in order tomaintain customer satisfaction with the unlimited buffet.
Keywords: Hospitality Management